The Concept of Forgiveness as a Tool in Counseling Intervention for Well-being Enhancement - Dini Farhana Baharudin; Mohd Rushdan Mohd Jailani; Muhammad Asyraf Che Amat; Melati Sumari (PERKAMA, 2024)
Throughout the history of mental health and well-being research, the pre-dominant focus of study has been pathological in nature. However, a trend toward the study of positive well-being has taken hold in the mental health field recently and one such concept is forgiveness. Forgiveness is considered a human strength and an important factor that influences human development. Based on previous research, in general, both lay person and therapists consider forgiveness to be beneficial and therapeutic. This paper tries to look at the conceptualization of forgiveness, models of forgiveness and factors that affects forgiving. Counseling implications and future research directions are also discussed.